The role of Kurdish women in science in the Middle Ages (Science of Hadith for example) Centuries (10-4 AD/16-10 AD) - Amin, Dr. Rahim Ahmad (Sulaimani Journal for Humanities, 2026)
The Kurdish nation is one of the nations that has played a great role in the development of the sciences of Islamic civilization throughout the history of the Islamic era. Kurdish women have had their own position in the field of sciences, not only students or teachers in schools, but also built many schools and scientific institutions with their wealth and heritage, where many famous scientists were educated.
Keywords: Kurdish Muslim Women; Middle Ages; Science of Hadith; Islamic Civilization